Female squirrel monkeys as models for research on women's pelvic floor disorders. (December 2021) - Pereira da Silva, Gessiane; Souza Pereira, Thyago Habner de; Felipe Lima, Ana Kelen; Russiano Vicente, Wilter Ricardo; Kuehl, Thomas J.; Ruiz, Julio Cesar; Barros Monteiro, Frederico Ozanan
Animal models enable research on biological phenomena with controlled interventions not possible or ethical in patients. Among species used as experimental models, squirrel monkeys ( Saimiri genus) are phylogenetically related to humans and are relatively easily managed in captivity. Quadrupedal locomotion of squirrel monkeys resembles most other quadrupedal primates in that they utilize a diagonal sequence/diagonal couplets gait when walking on small branches. However, to assume a bipedal locomotion, the human pelvis has undergone evolutionary changes. Therefore, the pelvic bone morphology is not that similar between the female squirrel monkey and woman, but pelvic floor support structures and impacts of fetal size and malpresentation are similar. Thus, this review explores the pelvic floor support structural characteristics of female squirrel monkeys, especially in relation to childbirth to demonstrate similarities to humans.